Effects of 12-months treatment with zoledronate or teriparatide on intima-media thickness of carotid artery in women with postmenopausal osteoporosis: A pilot study. (January 2019) - Passeri, Elena; Mazzaccaro, Daniela; Sansoni, Veronica; Perego, Silvia; Nano, Giovanni; Verdelli, Chiara; Lombardi, Giovanni; Corbetta, Sabrina
Atherosclerosis and osteoporosis are interrelated entities and share similar pathogenic mechanisms. Recent studies showed that key proteins of bone metabolism, such as osteoprotegerin (OPG) and osteopontin (OPN), are also involved in vascular atherosclerosis and calcifications. The carotid intima-media thickness (CA-IMT) is an early quantitative marker of generalized atherosclerosis. Aim of study was to investigate whether 12-months treatment with zoledronate (ZLN) or teriparatide (TPT) affects CA-IMT and circulating OPG and OPN levels. In this study, 11 postmenopausal osteoporotic women (aged 73, 70.5–74.5 years; median, range interquartile) treated with 5 mg/year iv ZLN; 9 postmenopausal osteoporotic women (aged 70, 62.5–73.5 years) treated with 20 µg/day sc TPT; and 10 aged-, body mass index (BMI)-, glycemic, and lipid profiles-matched, free from anti-osteoporotic and hypocholesterolemic drugs, controls were prospectively investigated at baseline and after 12 months. At baseline, median CA-IMT was similar in the three groups and increased after 12 months. CA-IMT increased significantly in TPT-treated patients (1.0, 0.8–1.2 vs 1.1, 0.9–15 mm, P  = 0.04), though the change was minimal. After 12 months of treatment, CA-IMT positively correlated with alkaline phosphatase (ALP) levels (r = 0.767, P  = 0.008) and negatively with high-density lipoprotein (HDL) cholesterol levels (r = −0.65, P  = 0.03), suggesting interplay between active bone remodeling and lipid profile. At baseline and after 12 months, median serum OPG and OPN levels did not differ among the groups and did not correlate with changes in CA-IMT. In conclusion, ZLN and TPT treatments are safe on carotid walls in osteoporotic women with subclinical atherosclerosis; circulating OPG and OPN are not affected by long-term anti-osteoporotic treatments and do not correlate with CA-IMT.